Ghrelin and Obestatin Levels in Serum and Saliva of Patients with Osteoporosis and the Effect of Strontium Ranelate - Celikbag, Bahar; Akgol, Gurkan; Aydin, Suleyman; Kamanli, Ayhan (Baycinar Medical Publ-Baycinar Tibbi Yayincilik, 2014)
Objective: It is known that Ghrelin and obestatin have effects on bone metabolism. In this prospective study it is aimed to assess serum and saliva ghrelin and obestatin levels in patients with post-menopausal osteoporosis in comparison to non-porotic healthy controls, and to determine the changes in these levels with strontium ranelate treatment. Material and Methods: Thirty-six drug-naive patients with postmenopausal osteoporosis and 21 healthy age-matched postmenopausal controls were included. Saliva and blood were collected to assess ghrelin and obestatin. Bone mineral density (BMD) was assessed using dual-energy X-ray absorptiometry. Strontium ranelate (2 g/day) and calcium (1200 mg/day) + vitamin D (800 IU/day) treatment were given to the osteoporotic patients for 6 months. Results: In patients with post-menopausal osteoporosis, saliva ghrelin levels were significantly higher and obestatin levels were significantly lower than controls at baseline (p<0.05). No significant difference in serum and saliva ghrelin or obestatin levels were achieved with the treatment (p>0.05). Lumbar and femoral BMD increased at the end of 6 months of treatment. Conclusion: Our results indicate that ghrelin and obestatin levels are key peptides that are need to be investigated in the bone metrabolism as well as in pathogenesis of osteoporosis.
Osteoporozlu hastalari{dotless}n serum ve tükürüklerinde ghrelin ve obestatin düzeyleri ve stronsiyum ranelati{dotless}n etkisi
Keywords: Postmenopausal osteoporosis; ghrelin; obestatin; strontium ranelate